Perinatal Mental Health Problems in Rural China: The Role of Social Factors - Jiang, Qi; Guo, Yian; Zhang, Evelyn; Cohen, Nourya; Ohtori, Mika; Sun, Adrian; Dill, Sarah-Eve; Singh, Manpreet Kaur; She, Xinshu; Medina, Alexis; Rozelle, Scott D. (Frontiers in Psychiatry, 2021)
Background: Perinatal mental health is important for the well-being of the mother and child, so the relatively high prevalence of perinatal mental health problems in developing settings poses a pressing concern. However, most studies in these settings focus on the demographic factors associated with mental health problems, with very few examing social factors. Hence, this study examines the prevalence of the depressive, anxiety and stress symptoms among pregnant women and new mothers in rural China, and the correlations between these mental health problems and social factors, including decision-making power, family conflicts, and social support. Methods: Cross-sectional data were collected from 1,027 women in their second trimester of pregnancy to 6 months postpartum in four low-income rural counties in Sichuan Province, China. Women were surveyed on symptoms of mental health problems using the Depression, Anxiety, and Stress Scale (DASS-21) and social risk factors. Multivariate logistic regression analyses were conducted to examine social risk factors associated with maternal mental health problems, with results reported as odds ratios (OR) and 95% confidence intervals (CI). Results: Among all respondents, 13% showed symptoms of depression, 18% showed symptoms of anxiety, 9% showed symptoms of stress, and 23% showed symptoms of any mental health problem. Decision-making power was negatively associated with showing symptoms of depression (OR: 0.71, CI: 0.60-0.83, p<0.001) and stress (OR=0.76, CI: 0.63-0.90, p=0.002). Family conflict was positively associated with depression (OR=1.53, CI: 1.30-1.81, p<0.001), anxiety (OR=1.34, CI: 1.15-1.56, p<0.001), and stress (OR=1.68, CI: 1.41-2.00, p<0.001). In addition, social support was negatively associated with depression (OR=0.56, CI: 0.46-0.69, p<0.001), anxiety (OR=0.76, CI: 0.63-0.91, p=0.002), and stress (OR=0.66, CI: 0.53-0.84, p<0.001). Subgroup analyses revealed that more social risk factors were correlated with symptoms of anxiety and stress among new mothers compared to pregnant women. Conclusion: Perinatal mental health problems are relatively prevalent among rural women in China and are strongly associated with social risk factors. Policies and programs should therefore promote individual coping methods, as well as target family and community members to improve the social conditions contributing to mental health problems among rural women.